CREATION OF RESOURCE-SAVING TECHNOLOGICAL PROCESS OF ELECTROSLAG SMELTING OF CYLINDRICAL BILLETS OF BIG DIAMETER OF STEEL OF NEW GRADE 5H3NMFS WITH USE OF STEEL BAR - V. N. Fedulov (Литьë и металлургия)
The new principles of creation of instrumental steel grades, which will allow to increase resource of outfil and will make it possible to use steel scrap fo r melting of new billers are developed